1990
DOI: 10.1210/endo-127-3-1234
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-2 Is a Potent Inhibitor of Ley dig Cell Steroidogenesis*

Abstract: Interstitial tissue of the testis consists of Leydig cells, macrophages, lymphocytes, plasma cells, mast cells and fibroblasts. Previously we have reported that interleukin-1 (IL-1) inhibits Leydig cell androgen production. In the present study, the effect of IL-2 was investigated. Leydig cells (10(5) cells/ml) from adult Sprague-Dawley rats were cultured with or without IL-2 for 24 h. After medium changes, human CG (hCG), 8-bromo-cAMP, or forskolin was added with or without IL-2. Cultures were continued for a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0
2

Year Published

1992
1992
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(24 citation statements)
references
References 32 publications
2
20
0
2
Order By: Relevance
“…IL-2-induced increase in ATR-18 immunostaining observed in this study is almost comparable with that reported about the lymphocytes [10,14,23,30]. It is of value to be indicated that IL-2 used in this study was at the half-maximum effective concentration which induced corticosterone biosynthesis in our previous adrenal cell culture study [12]. In this study, we compared the time courses of IL-2 stimulated prostaglandin E2, cyclic AMP and corticosterone synthesis in dispersed rat adrenal cells and found that prostaglandin E2 synthesis began to increase within an hour but the stimulation of cyclic AMP and corticosterone synthesis needed more than 12 hr to be induced [27].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…IL-2-induced increase in ATR-18 immunostaining observed in this study is almost comparable with that reported about the lymphocytes [10,14,23,30]. It is of value to be indicated that IL-2 used in this study was at the half-maximum effective concentration which induced corticosterone biosynthesis in our previous adrenal cell culture study [12]. In this study, we compared the time courses of IL-2 stimulated prostaglandin E2, cyclic AMP and corticosterone synthesis in dispersed rat adrenal cells and found that prostaglandin E2 synthesis began to increase within an hour but the stimulation of cyclic AMP and corticosterone synthesis needed more than 12 hr to be induced [27].…”
Section: Discussionsupporting
confidence: 90%
“…Among them, IL-2, originally identified as a T cell growth factor, has been reported to affect neuroendocrine functions, stimulating the pituitary-adrenocortical (P-A) axis [4,5,[7][8][9]17] and catecholamine release [7], and suppressing luteinizing hormone [29], testosterone [12] and melatonin levels [16]. No influence was reported on insulin levels [7], and effects on pituitary growth hormone, prolactin, thyroid-stimulating hormone, and folliclestimulating hormone releases are not conclusive [15,16,29].…”
Section: Introductionmentioning
confidence: 99%
“…A role for in¯ammatory cytokines (IL-1 and IL-2) is possible, as suggested by experimental studies (74,75). It may be considered appropriate that the secretion of anabolic androgens be switched off in circumstances of acute stress, in order to reduce the consumption of energy and substrates for, at that time at least, less vital functions.…”
Section: Luteinizing Hormone±testosterone Axismentioning
confidence: 99%
“…The reason for decreased T is the inhibition of testicular androgenesis or central LHRH secretion or both. Cytokines have been shown to take part in either situation [17,18]. Our patients had high CRP concentrations and APACHE II scores that prove the presence of inflammation and disease severity.…”
Section: Discussionmentioning
confidence: 51%